PWE-071 Safe Sedation in Endoscopy: Time for a New Approach?. (4th June 2013) - Zakeri, N; Webster, S; Coda, S; Humphries, A; Thillainayagam, A V
Abstract : Introduction: Despite increasing awareness of the potential hazards of endoscopic sedation, complications from sedation remain a major concern. Serious harm or death resulting from sedation overdose is now a Department of Health 'never event' 1 . Previous work by our group (2000–2005) demonstrated a steady sedation reversal incidence of 0.27%. Trust guidelines, in line with the current British Society of Gastroenterology safe sedation guidelines (2003) 2, were developed in 2005 (revised 2011). We present the results of a retrospective survey, evaluating whether the incidence and risk factors for sedation reversal events have changed. Methods: Our Trust is a large tertiary referral endoscopic centre across 3 sites. A retrospective analysis of all endoscopy (n = 73, 989) was performed, including all sedated endoscopic procedures carried out between 2007 and 2012 (n = 52, 553). Flumazenil or naloxone administration was used as a marker of sedation overdose requiring reversal. The results were compared to the previous single-site audit of 2000 to 2005 (n = 20, 569). Reversal episodes were analysed for associations with total sedation dose given, patient ASA grade, age and procedure undertaken. Statistical analysis was carried out using chi squared test and the linear regression model (Origin®). Results: In total 149 sedation reversals were recorded, representing 0.28% of all sedated endoscopic procedures, with no significant difference from the reversal rate (0.27%) recorded between 2000 and 2005 (p = 0.79). Mean dose of midazolam used in reversal events was 3.1mg (range 0.5–14mg). Mean dose of opioid (as pethidine equivalent) was 47.9mg (range 12.5–150mg). Higher than recommended doses of midazolam (5mg) or opioid (pethidine equivalent 50mg) were administered in 7.4% and 6.7% of reversal events, respectively. Endoscopic Retrograde Cholangiopancreatography (ERCP) was most associated with sedation reversal (1%). Mean dose of midazolam varied by procedure type and was highest for ERCP (5.1±2.9mg) and lowest for flexible sigmoidoscopy (1.7±0.6mg; p < 0.01). Mean dose of pethidine or opioid equivalent was highest for ERCP (78±38.7mg) and lowest for colonoscopy (33±13.4mg; p < 0.01). Sedation reversal was positively associated with increasing patient ASA grade (p < 0.05). Conclusion: Despite the emergence of national and local guidelines, aimed at safe sedation practise, there was no decline in our Trust's rate of sedation reversals over the last 12 years. Furthermore, the findings suggest there is a subgroup of patients, and a subset of endoscopic procedures, which still carry a significant risk of oversedation requiring reversal. This may support the growing interest in alternative sedation strategies for prolonged therapeutic endoscopic procedures such as ERCP. Disclosure of Interest: None Declared. References: DOH 'Never Events' 2012/13 Safety and Sedation During Endoscopic Procedures, BSG 2003.